Answer:-7
Step-by-step explanation:do absolute value first and then put the negative sign
If f(x)=x+1 and then x became 2, you would have the function f(x)=3. So basically for that function you would be going up three over 1. That function is already g(x)=4x. If X became 2, you would have g(x)=8x. The rate of up 8 and then over one. Because of that, g(x) would be higher
Answer:
x + Y = 39 or x = 39-y
20x + 50y = 1.40
20 (39 - y) + 50y = 11.40
7.80 - 20y + 50y = 11.40
30y = 11.40 - 7.80
30y = 3.60
y = 3.60/30
y = 12 50p coins were collected.
x = 39 - 12 = 27 20p coins were collected.
Proof:
20*27 + 50*12 = 11.40
5.40 + 6 = 11.40
11.40 = 11.40
I hope it helps.
Answer:
there is no way of solving this because the expression does not equal anything.
Step-by-step explanation: